MAIN FUNCTIONS, PRINCIPLES AND MODERN MODELS OF CULTURAL AND ARTS MANAGEMENT - Farrukh Ahmedov (International Journal of Literature and Language Studies, 2026)
Abstract: This topic covers the essence, main functions, management principles and modern management models of culture and art management. It also analyzes the role of planning, organization, motivation, coordination and control functions in the effective management of culture and art institutions. Innovative management approaches, strategic management, digital transformation and modern models of development of the sector based on international experience are considered.